Zmętnienie torebki tylnej soczewki w oczach pseudofakijnych – etiopatogeneza, obraz kliniczny, profilaktyka i leczenie - Łukaszewska-Smyk, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Posterior capsule opacification (PCO) is a late complication after the cataract surgery, currently occurring most often. The epithelial cells which migrate to the surface of the posterior capsule participate in the mechanism of PCO formation. Clinical opacification of the posterior capsule appears as the foggy form, creasing, pearl mass and fibrosis. PCO can be cured by laser or surgical capsulotomy. The factors influencing a size and intensity of PCO are as follows: age of patient, other diseases, method of surgery and type of the implanted artificial intraocular lens. Prevention against PCO during surgery should include accurate hydrodissection, removing of cortical mass, polishing of the capsule and intracapsular fixation of the lens. It is necessary to carry out further studies on possibilities of PCO prevention.